Secondary Cough Headache Responding to Topiramate - Dikici, Suber; Kocaman, Gulsen; Baltaci, Davut; Ercan, Nurten (My University, 2013)
Cough headache is a type of headache lasting one minute to 30 minutes and arising from activities, such as cough and Valsalva maneuver, which increase intra-abdominal pressure. It is seen in adults aged forty years and older. It is bilateral, intense and stabbing type of headache. Herein, we report the case of a 65-year-old patient presented with severe headache which was aggravated with defecation, lifting a heavy object and going up and downstairs. Her neurologic examination was normal. Magnetic resonance imaging revealed Arnold-Chiari malformation type 1. Surgical operation was planned, but she denied surgical operation. Indomethacin was not administered due to intractable dyspeptic complaints. Topiramate was administered to lower intracranial pressure. Her headache symptom considerably disappeared. Topiramate was stopped after 6 months, but her headache recurred. Hereupon, topiramate was re-administered. Headache symptom was quite relieved. We concluded that, topiramate could be medical alternative for secondary headaches, such as cough headache in case of Arnold-Chiari malformation type 1. (Archives of Neuropsychiatry 2013; 50: 82-83)